Sensory, microbiological, biochemical and physico-chemical assessment of freshness and quality of fresh Lake Malawi Tilapia (Chambo) stored in Ice - Kapute, F. (Bio Publishers, 2016)
Sensory, microbiological, biochemical and physico-chemical methods were used to assess freshness and quality of fresh Lake Malawi Tilapia (Local name: Chambo) to compare their effectiveness and reliability. Fresh Chambo samples were rejected by the sensory panel after 16 days from day of catch with a strong linear correlation (P < 0.01, R2 = 0.95) between sensory quality scores and storage time in ice. Highest bacterial load of 1.6×107 cfu/g, cfu/cm2 was observed on day 15 coinciding with sensory rejection time. TMA-N and TVB-N for freshly caught fish was 0.7 and 5.1 mg/100g, which increased to 3.4 and 26.4 mg/100g respectively at the time of sensory rejection also correlating with increased bacteria load in the fish. Initial pH of the fresh fish muscle was close to neutral (6.47), and reached its lowest point (5.84) on day 16 which was sensory rejection time. Findings suggest that sensory evaluation is reliable in the absence of the other methods. TMA-N is not a reliable method for assessing freshness quality of Lake Malawi Tilapia due to insignificant readings. pH showed to be a quick freshness indicator with an understanding that muscle pH for live fish is generally neutral and increases as deterioration of the quality of fish progresses in storage. Rejection of fish samples before reaching unacceptable microbial limits in this study, underpins the need for using more than one method for accurate freshness and quality assessments of fresh fish.